2020
DOI: 10.1038/s41598-020-60133-z
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA sequencing of rat hippocampus and human biofluids identifies acute, chronic, focal and diffuse traumatic brain injuries

Abstract: age-matched control serum. In these exploratory studies with rat and human tissues, we tested three hypotheses, 1) miRNA-seq profiles would identify TBI at all acute and chronic post-injury intervals, 2) miRNA-seq profiles would discriminate between focal and diffuse TBI and 3) serum miRNA-seq would reveal potential miRNA markers of neuropsychiatric and neurodegenerative sequelae. Methods Study design. The miRNA-seq and data analyses workflow is shown in Fig. 1A (rat studies) and Fig. 2A (human studies). Detai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 45 publications
(48 reference statements)
0
13
0
Order By: Relevance
“…We have selected hippocampus as it is the specific brain region critical for learning and memory process, and known to have significant association with the neuropsychiatric behavioral changes by various studies. Other previous studies had also extracted RNA from hippocampal tissue to examine the RNA changes in neurobehavioral insults and changes in cognition and memory 47 , 48 . After scopolamine treatment, mice showed decreased expression patterns of cholinergic genes ( Chrnb3 , Chrnb4 , Chat , Camk2b , Slc18a3 , Chrm1 ) compared to the vehicle, although statistical significances were lacking.…”
Section: Discussionmentioning
confidence: 99%
“…We have selected hippocampus as it is the specific brain region critical for learning and memory process, and known to have significant association with the neuropsychiatric behavioral changes by various studies. Other previous studies had also extracted RNA from hippocampal tissue to examine the RNA changes in neurobehavioral insults and changes in cognition and memory 47 , 48 . After scopolamine treatment, mice showed decreased expression patterns of cholinergic genes ( Chrnb3 , Chrnb4 , Chat , Camk2b , Slc18a3 , Chrm1 ) compared to the vehicle, although statistical significances were lacking.…”
Section: Discussionmentioning
confidence: 99%
“…Differentially expressed miRNAs were then screened from the RNA-sequencing results and a KEEG database analysis was performed. Based on KEEG analysis of miR-204-5p and its downstream predictive target genes and previous literature reports, it is concluded that miR-204-5p is associated with a variety of diseases related to the central nervous system [ 26 ]. Findings from previous reports revealed that miR-204-5p is involved in multiple signaling pathways and results from related studies have shown that miR-204-5p is involved with oxidative stress-related pathways, in specific to the oxidative capacity of mitochondria as demonstrated in vivo [ 27 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, no evidence of a correlation between hsa-miR-145-5p, or miR-335-3p and meningioma was reported till now. Notwithstanding, miR-145-5p is linked to psychiatric and neurodegenerative disorders [ 46 ]. Further, circPTN can sponge miR-145-5p to promote stemness or proliferation in glioma [ 47 ].…”
Section: Discussionmentioning
confidence: 99%